The role of self-help group in Jordan following treatment for breast cancer - Mahasneh, Deema (2015)
Background/Rationale: Breast cancer is the most common cancer in women worldwide. Recent findings found that self-help group is helpful for maintaining treatment regimens and coping with breast cancer and associated fears. However, there is a paucity of evidence on how a self-help group shapes women’s recovery, particularly in Jordan.